Nursing care in the post-operatory of cardiac surgery (Research, Society and Development, 2020)
The present study aimed to identify and evaluate nursing care in the postoperative period of cardiac surgery, a highly complex procedure with important organic repercussions, leading to a critical postoperative state and imposing intensive care for the individual's recovery. It is an integrative literature review carried out in the databases Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online and Excerpta Medica database. Studies published in Portuguese, English and Spanish between 2009 and 2019 that answered the guiding question were included. Among the results found, the monitoring of vital parameters, elaboration and implementation of nursing care plans, use of automated systems, use of standardized instruments and the importance of professional training for such use stand out. This evidence can provide subsidies for carrying out the nursing process and contribute to improving the care of this population.